Valproic acid extraction methods in human samples using gas chromatography: a review - Oliveira, Juliana Blume de; Santos, Bruno Pereira dos; Arbo, Marcelo Dutra (Drug Analytical Research, 2026)
Valproic acid (VPA) is widely used as an important drug for the treatment of epilepsy, seizures, bipolar disorders, and migraines. However, its narrow therapeutic range lead to risks of unintentional poisoning and potential suicide. Symptoms of VPA intoxication include drowsiness, hyperactivity, confusion, ataxia, coma, and sometimes can mimic brain death. Severe cases necessitate intensive care observation and evaluation of blood/plasma concentrations to determine the severity of poisoning. Analytical methods are crucial for monitoring drugs in biological fluids. This review aimed to describe the extraction methods used for the analysis of VPA in human biological samples using gas chromatography. Among 19 studies reviewed, liquid-liquid extraction (LLE), liquid phase microextraction (LPME), and solid-phase microextraction (SPME) are the most used extraction methods. Considering the laborious nature and large sample volumes required for LLE and solid-phase extraction (SPE), more efficient microextraction methods are needed. LPME, dispersive liquid-liquid microextraction (DLLME), air-assisted liquid-liquid microextraction (AALLME), and others offer promising alternatives. LPME, in particular, is favored ecologically due to reduced solvent usage compared to LLE. Novel approaches like dried blood spots (DBS) present emerging options for sample collection, helping in analytical and therapeutic monitoring contexts. Selection of extraction protocol hinges on method objectives, sample type, and laboratory capacity.